Pemberdayaan Posyandu Melalui Digitalisasi dan Penguatan Kapasitas Kader dalam Pencegahan Stunting di Desa Jabung Sisir - Ahmad Izzuddin; Nuzul Hikmah; Agustina Widayati; Yustina Suhandini Tj; Ira Aprilia; Andrik Sunyoto; Dyah Ariyanti; Faridahtul Jannah; Noer Fika Dita; Muhammad Hasan Fathul Arifin; Ali Masykur Ibrahim (Pusat Riset dan Inovasi Nasional, 2025)
Stunting is a serious health issue in Indonesia, with a national prevalence of 21.6 percent. Probolinggo Regency in East Java also records a high prevalence rate, reaching 17.3 percent. The main factors contributing to stunting are limited access to health services and nutrition. The Posyandu (Integrated Health Post) plays a crucial role in prevention efforts but faces challenges in management and cadre skills, particularly in data recording and nutritional status measurement. Jabung Sisir Village in Probolinggo Regency was selected as the community partner for empowerment through a program of Posyandu digitalization and cadre capacity building. The aim of this activity is to improve cadre literacy on stunting and to provide an effective digital reporting system to support prevention and control efforts. The implementation method consisted of cadre training on stunting literacy, anthropometric techniques, effective communication, and the use of a web- and Android-based Posyandu Information System. The program was followed by cadre mentoring as well as evaluation through pre-tests, post-tests, and periodic monitoring. The results showed an increase in cadre knowledge, anthropometric measurement skills, and the ability to use digital systems for data recording and reporting. These findings highlight that Posyandu digitalization can strengthen cadre capacity in stunting prevention while serving as an innovative model for enhancing community-based health services.